University Breadth Subject as an Entry to Chemical Engineering - Scholes, Colin A (Chemical engineering education, 2023)
Breadth subjects enable students to explore topics that are outside their core degree discipline and can be used to promote chemical engineering to non-engineering students. A breadth subject was created to be welcoming to all students, that presented energy issues through a chemical engineering context. Contact was through lectures, flipped classes and tutorials that were formulated to introduce engineering concepts. The subject was well received by students and a successful strategy to engage non-engineering students.